Penerapan Internet of Thing pada Aplikasi Mobile Smart Lot Parking - Fariyono, Fariyono; Wulandari, Fera Tri; Bahtiar, Arief Rais (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2022)
Public interest in shopping centers is very high. As a result, at certain times the shopping center parking lot is full. The full information on the building’s parking space which is not real-time makes the visitors disappointed. This delay in information can be a reputation for shopping center managers in serving potential visitors. Therefore, we need an information technology that can be accessed in real-time by potential visitors so that they are not deterred from coming to the shopping center. The purpose of this research is to design an empty parking lot guide application with a mobile-based Internet of Things. This application will later display information on the part of the parking lot that is still empty which can be monitored directly from smartphones.